2023
DOI: 10.2478/remav-2023-0004
|View full text |Cite
|
Sign up to set email alerts
|

Residential Real Estate as a Potential Hedge of Capital Against Inflation

Abstract: There is a belief among investors that real estate is an excellent way to protect capital from depreciation due to inflation. Research does not provide a clear answer as to whether this investors’ belief is correct, but some approaches indicate that simple econometric methods are not able, especially in the short term, to clearly indicate the existence of a relationship between inflation and property prices (Fogler, 1984). The purpose of the study –was to find the relationship between residential real estate p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 29 publications
1
4
1
Order By: Relevance
“…For the other investments, no such rela�onship could be demonstrated. These results are in turn close to those obtained with corresponding or similar methods on the Polish market by Fiszeder & Rowinski (2012), Kasprzak-Czelej (2015), or more recently Wolski (2022Wolski ( , 2023, but also by Stevenson and Murray (1999) on the Irish market. Leaving aside Bitcoin, which could not be studied before, the results achieved are in contradic�on with other studies (e.g., Fama and Schwert 1977, Lee & Isa 2019, Choi & Shin 2022.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…For the other investments, no such rela�onship could be demonstrated. These results are in turn close to those obtained with corresponding or similar methods on the Polish market by Fiszeder & Rowinski (2012), Kasprzak-Czelej (2015), or more recently Wolski (2022Wolski ( , 2023, but also by Stevenson and Murray (1999) on the Irish market. Leaving aside Bitcoin, which could not be studied before, the results achieved are in contradic�on with other studies (e.g., Fama and Schwert 1977, Lee & Isa 2019, Choi & Shin 2022.…”
Section: Discussionsupporting
confidence: 90%
“…It showed that in seven of the eight largest ci�es, property prices were posi�vely related to the infla�on rate. Wolski (2023) conducted a cointegra�on analysis using the Engle -Granger test. The study was carried out between the first quarter of 2009 and the fourth quarter of 2021, analysing the correla�ons between hedonic indices calculated by the Na�onal Bank of Poland for 6, 7 and 10 selected ci�es in Poland and infla�on rates -actual and forecast, published by the Sta�s�cs Poland and the Na�onal Bank of Poland.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Comparing the obtained results with other studies of the Polish market, we can recognize their correspondence with the results of Trojanek (2004) and Melnychenko et al (2022), indicating the inflationhedging ability of the Polish residential market. The discrepancy with the results of Wolski (2023), who concluded that the Polish residential market does not effectively hedge against inflation, is due to using different data and applying a different research method.…”
Section: Discussioncontrasting
confidence: 64%
“…Melnychenko et al (2022), using regression analysis, showed that, in the years 2009 -2021, in seven of the eight largest local housing markets in Poland, the real estate prices were positively related with the inflation rate. Wolski (2023) conducted a cointegration analysis for 2009-2021. Using three aggregated hedonic price indices of residential real estate (for 6, 7 and 10 of the biggest Polish cities), he stated that residential property prices and inflation rates (actual and expected) were not cointegrated, so Polish housing markets do not effectively hedge against inflation.…”
Section: Realmentioning
confidence: 99%
“…Residential real estate prices are also influenced by the prices of construction materials and the prices of land for housing development [10], [11]. Real estates were compared with other financial assets as potential hedge during high inflation [12]- [14]. Another interesting aspects deal with the impact of the COVID-19 pandemic on the housing market [15]- [17], detecting house price bubbles [18] and Pearson correlation between real estate markets in different countries.…”
Section: Introductionmentioning
confidence: 99%